2023
DOI: 10.3390/pharmaceutics15051528
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Responsive Hyaluronan-Based Hydrogels Combined with Allogeneic Cytotherapeutics for the Treatment of Osteoarthritis

Abstract: Thermo-responsive hyaluronan-based hydrogels and FE002 human primary chondroprogenitor cell sources have both been previously proposed as modern therapeutic options for the management of osteoarthritis (OA). For the translational development of a potential orthopedic combination product based on both technologies, respective technical aspects required further optimization phases (e.g., hydrogel synthesis upscaling and sterilization, FE002 cytotherapeutic material stabilization). The first aim of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…HA-L-pNIPAM copolymers (HA-L-pNIPAM 0.10 , HA-L-pNIPAM 0.25 , HA-L-pNIPAM 0.50 ) were synthesized using a slightly modified procedure based on a previous publication [ 33 , 34 ]. The scheme for the green chemistry synthetic route of the HA-L-pNIPAM copolymers is presented in Supplementary Materials (Figure S1) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HA-L-pNIPAM copolymers (HA-L-pNIPAM 0.10 , HA-L-pNIPAM 0.25 , HA-L-pNIPAM 0.50 ) were synthesized using a slightly modified procedure based on a previous publication [ 33 , 34 ]. The scheme for the green chemistry synthetic route of the HA-L-pNIPAM copolymers is presented in Supplementary Materials (Figure S1) .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a novel technology that involved a specific conjugation of the thermoresponsive polymer, poly(N-Isopropylacrylamide) (pNIPAM), to the linear HA backbone via a cyclooctyne linker (L) was reported [ 33 , 34 ]. Due to the desolvatation of the hydrophobic pNIPAM moieties above a defined lower critical solution temperature (LCST) and to the presence of the linker, the synthetic HA-L-pNIPAM copolymer spontaneously forms submicron spherical particles above the LCST [ 33 , 34 , 35 , 36 ]. These domains act as inter-chain crosslinkers, resulting in a sol–gel copolymer transition driven only by physical interactions, avoiding the use of chemical cross-linking agents.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, extensive technical work has validated the applicability of such cells in industrial-scale manufacturing workflows for transposition to GMP manufacturing [ 50 ]. Furthermore, previous preclinical research has shown the versatility and high potential of FE002 primary chondroprogenitors as promising contenders in cell-based orthopedic regenerative medicine [ 50 , 51 , 52 , 53 , 54 , 81 ]. Some of the advantages of using such an allogeneic cellular active substance for cartilage bioengineering involve the off-the-freezer availability of standardized biologicals, rationalized manufacturing workflows, and drastically reduced operative burdens [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, a large body of scientific and technical research regarding the clinical-grade allogeneic FE002 primary chondroprogenitor cell source is currently available. Notably, the in vitro and in vivo safety of the FE002 cells has been studied and validated by several research groups [ 50 , 51 , 52 , 53 , 54 ]. Based on the presented technical data and the current clinical developments of autologous and allogeneic cell-based solutions for knee chondral lesion management, a pilot clinical trial is being devised around the therapeutic FE002 progenitor cell source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation